A toxic triad : Aggression, anger and authoritarianism - A study with multiplayer online battle arena game players - Kordyaka, Bastian (Germany, 2025)
Previous research on players’ toxic behaviors in multiplayer online battle arena games (MOBAs) has suggested that individual beliefs about how other players “ought to behave” are major contributors to how they perceive and experience toxicity. In this study, we operationalized a psychometric measure of authoritarianism as a proxy for capturing players’ beliefs about the rigidity of roles and behavioral expectations in the MOBAs League of Legends and Dota 2. Using reasoning from frustration-aggression theory, we formulated hypotheses which we tested with a cross-sectional sample (N=216). The results offered support for our hypothesis that those scoring higher on authoritarianism also reported experiencing higher levels of anger and aggression in MOBAs. This study is among the first to offer empirical support that strong beliefs about rigid roles and behavioral patterns may lead to increased frustration and, consequently, toxic behavior. © 2024 Copyright for this paper by its authors.
Proceedings of the 8th International GamiFIN Conference, Ruka, Finland, April 2-5, 2024